The Architect, the Writer, and the Detective: Gianni Biondillo's Milan from the Margins, or the Education of the Gaze. Issue 2 (3rd April 2018) - Modena, Letizia
ABSTRACT: Scholars are actively reflecting on how the narrative viewpoint found in city fiction endorses alternative ways of seeing, describing, and constructing urban space. Their assumption is that fiction writers can better scope out and explain to us metamorphoses in the contemporary urban environment. Gianni Biondillo, the Milanese architect and author of crime fiction and essays on the city, breaks with the tradition of Milanese noir by redeeming the urban periphery from stereotypes that exile marginal neighborhoods and their residents. By setting his fiction in Quarto Oggiaro, Bovisa, and other peripheral neighborhoods of Milan, he draws readers into a dialogue about urban identity, community, and citizenship. This study analyzes several narrative and epistemological features of his detective fiction through which Biondillo intervenes in ongoing debates about the future of the city. His topographical and architectural descriptions compel us to rethink urban residents' psychological and physical relationships with the built environment.